Pengaruh Harga, Lokasi dan Keberagaman Produk terhadap Keputusan Pembelian pada Mebel Putra Furniture Puger - Onky Yahya Dewanata; Budi Santoso; Jekti Rahayu (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of price, location and product diversity on purchasing decisions at Putra Furniture Puger Furniture, Jember Regency. The independent variabels used in this study are price, location and product variety, while the dependent variabel used is purchasing decisions. This research is a quantitative research, the population of this research is Putra Furniture Puger Furniture customers. The sample selection used purposive sampling, and there were 96 samples in this study. The analysis technique used in this study is multiple linear regression with the help of the SPSS25 program. Based on the results of the research that has been done, based on the results of the t-test, the price has a calculated t value of 5.139 and a significant value of 0.005. The location variabel has a calculated t value of 3.388 and a significance of 0.001. The product diversity variabel has a t-count value of 1.199 and a significance of 0.234. From the results of the study, it was concluded that price and location had a significant effect on purchasing decisions while product diversity had no significant effect on purchasing decisions Keywords: Price, Product Diversity, Purchase Decision, Location